THE SYRIAN QUESTION IN THE CONTEXT OF GEOPOLITICAL CONTRADICTIONS OF RUSSIA AND USA - Arushan Arushanovich Vartumyan; David Sergeyevich Fedotov (Современная наука и инновации, 2022)
The Syrian crisis is most difficult today an interlacing of geopolitical contradictions where the multi-vector interests of global players - the USA and Russia and regional find the collision: Saudi Arabia, Turkey, Iran. In article an attempt of the analysis of the causes of civil war in Syria and its influence on geopolitical safety not only on regional, but also at the international level is made.